Unleashing The Global Potential: The Impact of Quality of Life on Knowledge Spillover and Productivity Disparities - Ali, Naveed; Ullah, Zia; Khan, Sohrab; Khan, Khalid (Pakistan Journal of Humanities and Social Sciences, 2023)
The purpose of this study is to look into the relationship between knowledge spillover, productivity differences, and the impact of quality of life in different countries. In order to accomplish this goal, the econometric technique known as Cross Sectional Augmented Autoregressive Distributive Lag (CS-ARDL) is utilized throughout this work. The findings point to the existence of complementarities between knowledge spillovers and the factors of quality of life in terms of their influence on total factor productivity. The findings imply that there is a contribution of knowledge spillovers to the national level of production. On the other hand, the relationship between knowledge spillovers and domestic productivity is contingent on a predetermined level of human capital as well as economic liberty. Hence, countries with more developed human capital and high economic freedom get more benefited from knowledge spillovers. This study has far-reaching ramifications. These findings can be used by policymakers to develop policies and initiatives that emphasize quality of life improvements, provide a conducive climate for knowledge spillover, and support productivity development across nations. Such approaches could help reduce economic inequities and propel global progress toward sustainable and inclusive growth.